Small intestinal mucosal abnormalities using video capsule endoscopy in intestinal lymphangiectasia - Lin Lin; Kuiliang Liu; Hong Liu; Jianfeng Xin; Yuguang Sun; Song Xia; Wenbin Shen; Jing Wu (Orphanet Journal of Rare Diseases, 2023)
Abstract Background Intestinal lymphangiectasia (IL) is a rare protein-losing enteropathy caused by disorders of the intestinal lymphatics. There are only a few case reports and case series concerning the VCE (video capsule endoscopy) findings of IL. This work aimed to evaluate the VCE characteristics of small intestinal mucosal abnormalities in patients with IL, and to investigate the relationship between clinical and VCE characteristics. Methods Consecutive patients with IL who underwent VCE were enrolled in this retrospective study. The cases were classified into the white villi group and non-white villi group according to mucosal abnormalities detected by VCE. Clinical and endoscopic characteristics were investigated and analyzed. Results A total of 98 patients with IL with a median onset age of 26.3 ± 19.2 years were included. VCE revealed the following small intestinal lesions: (i) white villi type (57/98, 58.2%), i.e.: white-tipped or granular villi, white nodular villi or plaques; (ii) non-white villi type (41/98, 41.8%), i.e.: diffused low and round villi; (iii) complications (46/98, 46.9%), i.e.: bleeding, ulcers, protruding or vesicular-shaped lesions, stenosis and lymphatic leakage. A total of 58.2% (57) and 41.8% (41) of the cases were classified into the white villi and non-white villi groups respectively. The percentage of chylothorax in the white villi group was significantly lower than that in the non-white villi group (12/57 vs. 19/41, p = 0.008). In VCE, there were no significant differences in the involved segments and total detected rate of complications between the white villi and non-white villi groups (p > 0.05), while the detected rate of lymphatic leakage in the white villi group was significantly higher than that in the non-white villi group (31.6% vs. 12.2%, p = 0.026). Conclusions Our study evaluated the entire small intestinal mucosal abnormalities of IL by VCE, especially endoscopic complications. IL has specific VCE abnormalities in addition to classical endoscopic findings.